BTS guideline for the investigation and management of malignant pleural mesothelioma. Issue 1 (14th February 2018) - Woolhouse, Ian; Bishop, Lesley; Darlison, Liz; Fonseka, Duneesha de; Edey, Anthony; Edwards, John; Faivre-Finn, Corinne; Fennell, Dean A; Holmes, Steve; Kerr, Keith M; Nakas, Apostolos; Peel, Tim; et al.
Abstract : The full guideline for the investigation and management of malignant pleural mesothelioma is published in Thorax . The following is a summary of the recommendations and good practice points. The sections referred to in the summary refer to the full guideline.